Modified Backscatter Communication Model for Wireless Communication Network Applications - Chen, Joy Iong Zong (IRO Journal on Sustainable Wireless Systems, 2021)
The green communication and large-scale connection issues will be faced by the wireless communication networks with futuristic sixth generation (6G) technology. The radio-frequency (RF) and spectrum sources may be shared simultaneously to achieve optimal communication in these networks by means of backscatter devices (BD) that may function in constrained spectrums as well as the stringent energy scenarios of green Internet-of-things (IoT) by means of the proposed novel modified backscatter communication model (BCM). Unlicensed eavesdroppers may interfere with the BD due to its vulnerability caused by the wireless communication channels and their broadcasting nature. The intrusion of an unlicensed eavesdropper is detected in an efficient manner by means of the proposed BCM. The analytical derivations of intercept probability (IP) and outage probability (OP) are invoked to analyze the security and reliability of the proposed architecture. Under high main-to-eavesdropper ratio (MER) regime, the IP and under high signal-to-noise ratio (SNR) regime, the OP asymptotic behaviors are estimated additionally. Based on the results of performance evaluation, it is evident that there is a decrease in the security of BD with the increase in MER while there is a simultaneous increase in the legitimate user security. Various system parameters may be adjusted for optimizing the security and reliability performance trade-off. For diverse orders, the existence of error floors are indicated by the non-zero fixed constant of BD and the legitimate user’s OP when high SNR value is observed at the system.
Keywords: Intercept probability; Outage probability; Internet of Things; Wireless communication network; Backscatter devices